2010
DOI: 10.1039/c0jm00354a
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared absorbing and luminescent gold speckled silica nanoparticles for photothermal therapy

Abstract: Herein, we report the development and functional evaluation of sub-50 nm near-infrared absorbing and luminescent gold speckled silica (GSS) nanoparticles for fluorescence traceable and selective, in vitro and in vivo photothermal ablation applications. The nanoparticles prepared using microemulsion-mediated approach, are comprised of GRAS (generally regarded as safe) materials, and are promising multifunctional agents for image guided photo-mediated therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 29 publications
0
30
0
Order By: Relevance
“…Numerous studies have demonstrated the efficacy of these nanomaterials for tumor ablation in vitro. 2,7,8,13 Several studies have focused on the effect of photothermal therapy using these nanomaterials using in vivo models. 1,10,13 These in vivo studies have demonstrated that a single photothermal treatment results in partial but incomplete tumor destruction based on long term follow-up of tumor growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have demonstrated the efficacy of these nanomaterials for tumor ablation in vitro. 2,7,8,13 Several studies have focused on the effect of photothermal therapy using these nanomaterials using in vivo models. 1,10,13 These in vivo studies have demonstrated that a single photothermal treatment results in partial but incomplete tumor destruction based on long term follow-up of tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…6 Numerous nanomaterials including nanoshells, 1,2 polyhydroxy fullerenes, 5 gold speckled silica nanoparticles (NPs), 7 gold NPs, 8 gold nanorods, 3 nanotubes, 9,10 nanocages, 11 and quantum dots 12 have been investigated as anticancer photothermal agents. Numerous studies have demonstrated the efficacy of these nanomaterials for tumor ablation in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…For breast cancer, intratumoral delivery could involve direct intratumoral injection of nanoparticles guided by traditional imaging [ultrasound, magnetic resonance imaging (MRI), or mammography] 10. Advantages of this approach are restricted exposure of delivered nanomaterials to diseased sites.…”
Section: Delivering Nanomaterials To Breast Cancer Sitesmentioning
confidence: 99%
“…A number of nanomaterials are active photothermal agents including gold speckled silica nanoparticles, nanoshells, nanorods, nanocages, and nanotubes 2. Sharma et al 10 have recently demonstrated the efficacy of gold speckled silica nanoparticles as multifunctional photothermal cancer agents in a murine model of breast cancer (Fig. 1).…”
Section: Non‐invasive Treatment Of Breast Cancermentioning
confidence: 99%
“…7,8 Therefore a facile route to synthesize nanosized metallic particles has become highly desirable. 22,35,[46][47][48] Inspired by these considerations, this work aims to synthesize silica nanotube (SNT)-supported noble metallic nanoparticles (i.e., Au, Ag, and Pd) under ambitious conditions and explore their catalytic activity in the reaction of 4-nitrophenol reduction by sodium borohydride. As the particle size is reduced, the surface energy of nanoparticles increases, making them unstable with high tendency for inter-particle aggregation.…”
Section: Introductionmentioning
confidence: 99%